2016
DOI: 10.1177/2473011416s00055
|View full text |Cite
|
Sign up to set email alerts
|

Effect of First Ray Insufficiency and Metatarsal Index on Metatarsalgia in Hallux Valgus

Abstract: Category: Midfoot/Forefoot Introduction/Purpose: There are two concepts that tried to explain the etiology of metatarsalgia in hallux valgus patients: First, the one that states that as the magnitude of hallux valgus increases, there is a mechanical overload of the lesser metatarsals. Second, that an increased relative lesser metatarsal length is a factor in the development of metatarsalgia. However there is no current evidence that these facts predisposes for primary metatarsalgia. The purpose of the study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
2

Year Published

2016
2016
2016
2016

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
0
3
0
2
Order By: Relevance
“…After all, a long second metatarsal will not, by itself, be sufficient to produce a tear. Rather, most tears will depend on the interplay of both suboptimal genetics (eg, foot structure and function) 27 and hazardous environmental conditions (eg, activity and shoe gear). Future work may explore the potential interactive effects of metatarsal length and these other factors (e.g., tight Achilles tendon, cavus foot type, high-heeled shoe gear).…”
Section: Discussionmentioning
confidence: 99%
“…After all, a long second metatarsal will not, by itself, be sufficient to produce a tear. Rather, most tears will depend on the interplay of both suboptimal genetics (eg, foot structure and function) 27 and hazardous environmental conditions (eg, activity and shoe gear). Future work may explore the potential interactive effects of metatarsal length and these other factors (e.g., tight Achilles tendon, cavus foot type, high-heeled shoe gear).…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between the first and second metatarsal showed that 27 patients had index minus formula (if first metatarsal was shorter than second), 5 index plus (first metatarsal longer than second), and 20 index plus-minus (first and second metatarsal of equal length). 34…”
Section: Methodsmentioning
confidence: 99%
“…The relationship between the first and second metatarsal showed that 27 patients had index minus formula (if first metatarsal was shorter than second), 5 index plus (first metatarsal longer than second), and 20 index plusminus (first and second metatarsal of equal length). 34 Groups were divided according to type of mechanical metatarsalgia. Sixteen cases (20.5%) had metatarsalgia of the second and third rocker, 44 (56.4%) had metatarsalgia of second rocker, and 18 (23.1%) metatarsalgia of third rocker (Table 1).…”
Section: Methodsmentioning
confidence: 99%
“…Dentro do grupo com metatarsalgia encontramos um subgrupo com hálux valgo (31%), achado compatível com a literatura, que mostra uma forte associação entre essas duas patologias 30,58,65 . Porém a repercussão da deformidade em valgo do hálux na disposição das cabeças dos metatarsais com carga no plano coronal não é clara.…”
Section: Caracterização Da Casuística Utilizadaunclassified
“…Muito se discute sobre a associação do hálux valgo com a instabilidade da 1ª articulação tarsometatarsal nos planos sagital e coronal, inclusive uma relação de causalidade entre a deformidade e a instabilidade, mas ainda não há consenso entre os autores [53][54][55][56]60,65,72,73 .…”
Section: Caracterização Da Casuística Utilizadaunclassified